ANALISIS DAYA OUTPUT GENERATOR BERDASARKAN VARIASI DEBIT AIR PADA PROTOTYPE PLTMH DENGAN TURBIN VORTEX - I Gusti Ngurah Agastya Citranath; Lie Jasa; I Made Suartika (Program Studi Teknik Elektro UNUD, 2022)
Vortex turbine is a reaction water turbine that can utilize energy from low headed waterway. The power output of generator on microhydro power plant will differ depend on the input parameters used, such as water flow rates. Hence, this research goal is to find out the power output of generator from various water flow rates with an artificial waterway on a vortex turbine within the microhydro power plant prototype. This research consist a free variable of water flow rates of 2,5 l/s, 3,5 l/s, and 4,5 l/s using 9 blades turbine and paralel load lamps. From the experiment, raises of water flow rate is proportional to the increase of generator’s power output. The power output generated by each water flow rates used are 0,085 W at 2,5 l/s water flow rate, 0,256 at 3,5 l/s, and 0,387 at 4,5 l/s. Based on the experiment, it can be concluded that the increase of input water flow rate is equal to the increase of the power output generated by the generator. It is caused by the rotation of the turbine will be adjusted by the water flow rate used.